2018
DOI: 10.3389/fimmu.2018.00473
|View full text |Cite|
|
Sign up to set email alerts
|

Long Non-Coding RNA HOXA Transcript Antisense RNA Myeloid-Specific 1–HOXA1 Axis Downregulates the Immunosuppressive Activity of Myeloid-Derived Suppressor Cells in Lung Cancer

Abstract: HOXA transcript antisense RNA myeloid-specific 1 (HOTAIRM1) is a long non-coding RNA that has been shown to be a key regulator of myeloid cell development by targeting HOXA1. Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that possess immunosuppressive function. However, the impact of HOTAIRM1 on the development of MDSCs remains unknown. In this study, we demonstrated that HOTAIRM1 was expressed in MDSCs and that overexpression of HOTAIRM1 could downregulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 35 publications
(28 reference statements)
2
81
0
Order By: Relevance
“…HOX antisense intergenic RNA myeloid 1 (HOTAIRM1) is a lncRNA with a length of 1052 bp. It was recently found to participate in various cancers, such as gastrointestinal malignancies [13][14][15][16] , breast cancer 17 , lung cancer 18 , glioblastoma multiforme 19 , and acute myeloid leukemia 20,21 . Of note, HOTAIRM1 is under-expressed in colorectal cancer 13 and gastric cancer 14 .…”
Section: Introductionmentioning
confidence: 99%
“…HOX antisense intergenic RNA myeloid 1 (HOTAIRM1) is a lncRNA with a length of 1052 bp. It was recently found to participate in various cancers, such as gastrointestinal malignancies [13][14][15][16] , breast cancer 17 , lung cancer 18 , glioblastoma multiforme 19 , and acute myeloid leukemia 20,21 . Of note, HOTAIRM1 is under-expressed in colorectal cancer 13 and gastric cancer 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the expression of HOTAIRM1 and its target gene HOXA1 were negatively associated with the ratio of MDSCs and ARG-1 levels in PBMCs of patients with lung cancer. Furthermore, HOTAIRM1 overexpression could decrease the immunosuppressive functions of MDSCs and suppress the induction of MDSCs from PBMCs of healthy control (72). Therefore, HOTAIRM1/HOXA1 might be a potential therapeutic target for lung cancer (72).…”
Section: Mdscsmentioning
confidence: 97%
“…Furthermore, HOTAIRM1 overexpression could decrease the immunosuppressive functions of MDSCs and suppress the induction of MDSCs from PBMCs of healthy control (72). Therefore, HOTAIRM1/HOXA1 might be a potential therapeutic target for lung cancer (72).…”
Section: Mdscsmentioning
confidence: 97%
“…Emerging evidences have shown that noncoding RNA (ncRNA) including micro RNA (miRNA), long noncoding RNAs (lncRNAs), and circular RNA are associated with inflammation and tumor, and exert certain regulatory effect on the differentiation and development of MDSCs . In inflammation‐induced tumor, miRNA promote MDSC immunosuppressive functions by activating transcription factor NF‐kB and STAT3 signal, so as to promote angiogenesis, EMT and metastasis, such as miR‐10a, miR‐21, miR‐17‐5p, miR‐20a, miR‐146a, miR‐181b, and so forth .…”
Section: Main Functional Characteristics Of Mdscsmentioning
confidence: 99%